Foot and mouth disease biosecurity and risk mitigation in auction markets: a scoping review - Hanthorn, Christy J.; Sanderson, Michael W. (Frontiers in Veterinary Science, 2026)
IntroductionFoot and mouth disease (FMD) is a highly contagious, viral vesicular disease affecting cloven-hoofed livestock species. The disease has negative impacts on livestock health and wellbeing as well as international trade opportunities for affected countries. The United States (U. S.), while currently free from FMD, has developed preparedness and response resources, including biosecurity guidance, for many livestock industry sectors with the aim of balancing robust disease control with business continuity. However, guidance on effective biosecurity strategies for auction markets is lacking.MethodsTherefore, the objective of this scoping review is to identify peer-reviewed literature that describes biosecurity strategies which decrease the risk of FMD introduction into auction markets or mitigation strategies that prevent FMD transmission from auction markets.ResultsEight reports were included in this review with six reports discussing FMD biosecurity risks from auction markets, and two reports discussing FMD outbreak mitigation strategies involving auction markets. No reports describing FMD biosecurity risks to or strategies for auction markets were identified for inclusion in this review.DiscussionThis review demonstrates the association between livestock movement through auction markets and FMD introduction risk to herds as well as the potential for auction markets to contribute to widespread dissemination of FMD in the absence of biosecurity strategies. Developing resources to address this current preparedness gap is a critical need illustrated by the evidence identified in this review. Effective biosecurity strategies and risk mitigation guidance for auction markets would substantially bolster the U. S. livestock industry’s resiliency in the event of an FMD incursion